The mechanics and regulation of market abuse : a legal and economic analysis - Avgouleas, Emilios (Oxford ; New York : Oxford University Press, 2005)
This book analyses the mechanics and regulation of two of the most harmful market practices in the modern financial world: insider dealing and market manipulation, which together comprise the offence of market abuse. Avgouleas examines the UK and EC regimes from an interdisciplinary perspective, also making extensive and critical use of US case law. He emphasizes the economic analysis of anti-fraud manipulation regulations and their effects upon market welfare and explores the possible deterrent benefits of civil law remedies.
Modern financial markets and finance theory -- Deconstructing and reconceptualizing market abuse -- The mechanics of market manipulation -- The regulation of market abuse -- The emerging EU regime for the regulation of market abuse -- The prohibition and punishment of market abuse in the UK -- Civil liability for market abuse in the UK -- Market abuse deterrence under a civil liability regime -- Concluding remarks and proposals for action.
Includes bibliographical references and index.
oif 02/03/15
Loan
Keywords: Insider trading in securities -- Law and legislation -- Great Britain; Insider trading in securities -- Law and legislation -- European Union countries; Insider trading in securities -- Law and legislation -- United States; Remedies (Law); Law reform